2011
DOI: 10.4236/jgis.2011.33019
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Spatial Mapping of Flash Flood Hazard in Makkah City, Saudi Arabia

Abstract: Flash floods occur periodically in Makkah city, Saudi Arabia, due to several factors including its rugged to-pography and geological structures. Hence, precise assessment of floods becomes a more vital demand in development planning. A GIS-based methodology has been developed for quantifying and spatially mapping the flood characteristics. The core of this new approach is integrating several topographic, metrological, geological, and land use datasets in a GIS environment that utilizes the Curve Number (CN) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…For the SCS method of predicting flooding, CN values are obtained from LULC features and vary with the type of LULC, so LULC plays a vital role in affecting and determining the runoff volume for sub-catchments. The results support the findings of Dawod et al (2011) who also concluded that the higher the CN values of sub-catchments were, the higher the runoff and flood hazards.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For the SCS method of predicting flooding, CN values are obtained from LULC features and vary with the type of LULC, so LULC plays a vital role in affecting and determining the runoff volume for sub-catchments. The results support the findings of Dawod et al (2011) who also concluded that the higher the CN values of sub-catchments were, the higher the runoff and flood hazards.…”
Section: Discussionsupporting
confidence: 89%
“…This may explain why some sub-catchments which had a lot of impervious areas were not flooded, for example sub-catchment 1. Dawod et al (2011) concluded that flow length is one of the main factors affecting runoff and flood risk in urban areas. Long et al (2010) argued that once flow length of sub-catchments increases, the values of bankfull discharge will be improved, and so the flood hazard will logically be reduced in areas with a high rate of flow length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dawod et al (2011) utilized the curve number (CN) method to model flash floods for ungauged arid catchments and then integrated the results with topographic, metrological, geological, and land use datasets in order to quantify and spatially map the flood characteristics; Bajabaa et al (2014) produced a flash flood hazard map by combining GIS techniques and physiographic features of the study area; Fernandez-Lavado et al (2007) derived flood hazard maps from a comprehensive geomorphological map, and classified flood hazards into three levels (very high, high, and moderate). In China, the main purpose of flash flood hazard mapping is currently to aid in community emergency planning, and flash flood hazard mapping is still at an early stage (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…The consequences of the floods vary from a medium with another and are primarily related to the distance which separates the urban areas, the agricultural lands and the installations of the floodplains [10], it is thus the preliminary study for the prevention against these risks of floods proves to be paramount for the protection or the reduction of the possible damage.…”
Section: History Of the Risings In Tunisiamentioning
confidence: 99%